Ventricular fibrillation induced by fever in structurally normal hearts - Ma, Ji-Fang; Zhou, You; Fu, Hai-Xia (Frontiers in Cardiovascular Medicine, 2023)
Ventricular fibrillation (VF) is a life-threatening arrhythmia that usually happens in patients with structural heart diseases. However, fever-induced ventricular fibrillation in structurally normal hearts was reported, and the four main diseases associated with these cases were Brugada syndrome, long QT syndrome, idiopathic ventricular fibrillation, and non-cardiovascular diseases. In this review, we analyzed this phenomenon and its clinical characteristics.